E-071 Using transcranial doppler ultrasound for the objective evaluation and prediction of endovascular treatment outcomes. (22nd July 2018) - Thibeault, C; Thorpe, S; Wilk, S; Devlin, T; Hamilton, R
Abstract : Introduction: The Thrombolysis In Cerebral Infarction (TICI) score remains a standard for reporting angiographic outcome after endovascular treatment of acute ischemic stroke. However, the TICI score has been shown to be a poor predictor of clinical outcome. Purpose: In this pilot study we explore the use of transcranial Doppler ultrasound as an adjunct to current measures of intervention success. TCD in these situations has the benefit of revealing the relevant hemodynamics while being non-invasive and safe. Materials and methods: Eight subjects (66±18.6 years) with LVOs confirmed by CT/A received TCD measurements of the middle cerebral arteries before and after undergoing surgical thrombectomy. Five of the patients also received tPA intravenously. Angiographic intracranial flow was graded on the TICI scale reported by the neuro-interventionist. The TCD beat waveforms were analyzed using the cerebrovascular waveform velocity curvature (CVFBc) metric. Curvature is a mathematical property of space curves which quantifies the degree to which a curve deviates from being straight. CBFVc is an application of that curvature metric specific to TCD, which quantifies the degree to which a beat morphologically deviates from normal. Results: All subjects were reported with a TICI score of 0 pre-intervention and a mean NIHSS score of 17±5.3. Post-intervention, the mean NIHSS was 11.25±7.9, with seven subjects graded 2B (filling at a diminished rate), and the remaining subject graded at 3 (complete perfusion). Despite successful outcome grades, five subjects had post NIHSS scores suggesting moderate to severe stroke (16.6±2.7), one was at a moderate level (6), and two scored at the minor level (0 and 1 respectively). This illustrates the well-known problem of recanalization rates not correlating with clinical outcomes. Figure 1 illustrates the change in CBFVc pre- (open circles) and post-intervention (solid circles) vs NIHSS (left), with example beats (right). The upper left and lower right quadrants delineate the regions where CBFVc correctly correlates with NIHSS. The upper right quadrant marks where CBFVc identified a non-pathological beat, however, the NIHSS score indicates dysfunction. The subjects in this region demonstrated a return to normal waveform morphology, but the damage was likely too great for a return to normal function. CBFVc analysis correctly predicted 6 of 8 subject outcomes, compared to the 2 of 8 predicted by TICI score alone. Conclusion: TCD has the potential to compliment current post-intervention outcome evaluation methods by non-invasively capturing clinically relevant cerebral hemodynamics. Disclosures: C. Thibeault: 4; C; Neural Analytics. 5; C; Neural Analytics. S. Thorpe: 5; C; Neural Analytics. S. Wilk: 4; C; Neural Analytics. 5; C; Neural Analytics. T. Devlin: 2; C; Neural Analytics. 4; C; Neural Analytics. R. Hamilton: 4; C; Neural Analytics. 5; C; Neural Analytics.